Pengembangan Video Pembelajaran pada Mata Pelajaran Alat dan Mesin Pertanian di SMK Negeri 4 Gowa - Saleh, Auliah Alifa Azzahra; Sukainah, Andi; Rahman, Khaidir (Jurnal Pendidikan Teknologi Pertanian, 2024)
This study is designed to develop and analyze the level of validation, student learning outcomes, and student responses to the use of video learning media. This research refers to research and development (R&D) using the ADDIE development model. The object of research is a learning video media product that was tested to 20 students in small groups, 2 media experts and 2 teaching material experts who evaluated and provided input related to learning video media and instruction books related to video material or content. The study response consisted of 30 grade X ATPH 3 students in a large group. The results showed that the results of media expert validation were in the "Very Valid" category with an average score of 3.8, while the results of material expert validation were in the "Valid" category with an average score of 2.67. From a small group of 20 students, 30% achieved results in the "Very Valid" category, 65% "Valid" and 5% "Less Valid". The average response result of the 30 large group students was 87.42 which was included in the "Very Good" category. Students in the experimental group who carried out the learning process with supporting media in the form of learning video media obtained a higher total average score compared to students in the control group who underwent the learning process without supporting media.